1995
DOI: 10.1074/jbc.270.22.13179
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Glycoprotein IIb-IIIa- and Aggregation-independent Mechanism of Phosphatidylinositol 3′,4′-Bisphosphate Synthesis in Human Platelets

Abstract: The synthesis of phosphatidylinositol 3',4'-bisphosphate (PtdIns(3,4)P2) in 32P-labeled human platelets induced by the tetrameric lectin concanavalin A and the physiological agonist thrombin were compared. Like thrombin, concanavalin A stimulated a time-dependent accumulation of PtdIns(3,4)P2, which reached maximal levels after 5 min of stimulation. However, while synthesis of PtdIns(3,4)P2 induced by thrombin was dependent on platelet aggregation, the production of PtdIns(3,4)P2 induced by concanavalin A was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…This model is also supported by our results on the effect of cytochalasin D on PtdIns(3,4)P 2 production induced by the lectin ConA. It is known that this lectin is a potent stimulator of actin polymerization and cytoskeleton reorganization, and promotes the synthesis of PtdIns(3,4)P 2 through a mechanism totally independent of platelet aggregation [7]. Thus, while two mechanisms for PtdIns(3,4)P 2 production are operating in thrombin‐stimulated platelets, aggregation‐independent and aggregation‐dependent, only the former one takes place in ConA‐treated platelets.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This model is also supported by our results on the effect of cytochalasin D on PtdIns(3,4)P 2 production induced by the lectin ConA. It is known that this lectin is a potent stimulator of actin polymerization and cytoskeleton reorganization, and promotes the synthesis of PtdIns(3,4)P 2 through a mechanism totally independent of platelet aggregation [7]. Thus, while two mechanisms for PtdIns(3,4)P 2 production are operating in thrombin‐stimulated platelets, aggregation‐independent and aggregation‐dependent, only the former one takes place in ConA‐treated platelets.…”
Section: Discussionsupporting
confidence: 86%
“…To confirm the correlation between the aggregation‐dependent and the cytochalasin D‐sensitive synthesis of PtdIns(3,4)P 2 , we analyzed 32 P‐labeled platelets stimulated with the lectin ConA. We have previously demonstrated that ConA induces the accumulation of PtdIns(3,4)P 2 exclusively through a mechanism independent of integrin α IIb ‐β 3 and aggregation [7]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Substantial evidence indicates that the syntheses of PtdIns-(3,4,5)P 3 and PtdIns(3,4)P 2 are regulated via distinct mechanisms (24)(25)(26)(27)(28), and that these two D-3 phosphoinositides play different functional roles. For example, PtdIns(3,4)P 2 † This work was supported in part by National Institutes of Health Grant R01 GM53448 and by American Heart Association, Kentucky Affiliate, Grant KY-97-GS-26.…”
mentioning
confidence: 99%
“…The ability of ConA to induce, even in the absence of platelet aggregation, events that in thrombin-treated platelets are normally observed only during aggregation is a tipical feature of this lectin. We have recently demonstrated, for instance, that activation of the phosphatidylinositol 3-kinase, which is largely dependent on aggregation in thrombin-stimulated platelets, occurs through an aggregation-independent mechanism in ConA-treated platelets (30). This peculiarity of ConA may be due to the tetrameric binding properties of lectin, which induces topographic changes on the cell surface reproducing events occuring during aggregation.…”
Section: Discussionmentioning
confidence: 99%